AB0180 The Role of Immune Regulation of CD4+CD52High T Cells in Systemic Lupus Erythematosus. (9th June 2015) - Umeda, M.; Koga, T.; Ichinose, K.; Tsuji, S.; Fukui, S.; Nishino, A.; Nakashima, Y.; Suzuki, T.; Horai, Y.; Hirai, Y.; Kawashiri, S.-Y.; Iwamoto, N.; et al.
Abstract : Background: CD52 is a cell-surface glycoprotein that is widely expressed in lymphocytes, monocytes and eosinophils. The anti-CD52 antibody has been used to treat multiple autoimmune diseases, and its effectiveness has been reported [1]. CD4+CD52high T cells inhibit the activation of CD4+CD52low T cells through the release of cell-surface CD52. Soluble CD52, which is cleaved from CD4+CD52high T cells, works as a ligand of siglec-10 on CD4+CD52low T cells [2]. The role of the immune regulation of CD4+CD52high T cells in systemic lupus erythematosus (SLE) is unknown. Objectives: We evaluated the CD4+CD52high T cells in the human peripheral blood mononuclear cells (PBMCs) of SLE patients and clarified their roles in the pathogenesis of SLE. Methods: We isolated the PBMCs of 33 SLE patients, 8 non-SLE patients (6 with rheumatoid arthritis, 2 with mixed connective-tissue disease) and 11 healthy controls (HCs). The expressions of CD4+CD25+CD127− T cells (Tregs), CD4+CD52high T cells and CD4+CD52low T cells were analyzed by flow cytometry. We also analyzed the correlations with clinical parameters including SLEDAI, anti-ds-DNA antibody titer and complement titer. The soluble CD52 was also analyzed in an ELISA among the SLE and non-SLE patients and HCs. Results: No significant difference was found in the population of CD4+CD25+ CD127− cells among the groups. There was no correlation between Tregs and CD4+CD52high T cells in SLE. We found that the expression of CD4+CD52low T cells of the SLE group were significantly correlated with SLEDAI (p-value=0.0485, r=0.346096). The expression of CD4+CD52low T cells in the SLE patients with high-SLEDAI (6>) was significantly higher than HC (p=0.0011) and non-SLE (p=0.0034). Soluble CD52 measured by ELISA was found to be decreased in the SLE group versus the other groups (vs. HC: p=0.0011; vs. non-SLE: p=0.0142). Conclusions: Collectively, our data indicate that increased CD4+CD52low T cells and decreased soluble CD52 may contribute to the development of SLE. Our findings suggested that CD4+CD52high T cells are involved in autoimmune diseases with different functions of Tregs. The determination of CD4+CD52low may contribute to evaluations of SLE's disease activity and may help elucidate the mechanisms underlying SLE. References: Rao SP, Sancho J, Campos-Rivera J, Boutin PM, Severy PB, Weeden T, Shankara S, Roberts BL, Kaplan JM. Human peripheral blood mononuclear cells exhibit heterogeneous CD52 expression levels and show differential sensitivity to alemtuzumab-mediated cytolysis. PLoS One. 2012 Jun;7(6):e39416. Bandala-Sanchez E, Zhang Y, Reinwald S, Dromey JA, Lee BH, Qian J, Böhmer RM, Harrison LC. T cell regulation mediated by interaction of soluble CD52 with the inhibitory receptor Siglec-10. Nat Immunol. 2013 Jul;14(7):741-8. Disclosure of Interest: None declared